Detection of Mycobacterium tuberculosis-derived DNA in circulating cell-free DNA from a patient with disseminated infection using digital PCR. (January 2018) - Yamamoto, Masaki; Ushio, Ryota; Watanabe, Hiroki; Tachibana, Takayoshi; Tanaka, Masatsugu; Yokose, Tomoyuki; Tsukiji, Jun; Nakajima, Hideaki; Kaneko, Takeshi
Highlights: A case of disseminated Mycobacterium tuberculosis (MTB) infection after hematopoietic stem cell transplantation is reported. Circulating cell-free DNA of the patient showed positive amplification for an MTB complex-specific sequence using a digital PCR technique. Other examinations using sputum, urine, and blood samples did not show the presence of MTB before samples were obtained at autopsy. The MTB infection was confirmed by positive acid-fast staining and an approved quantitative PCR assay on liver tissue obtained at autopsy. Thus, the detection of MTB from circulating cell-free DNA with this technique could be exploited as a less invasive and rapid diagnostic tool for pulmonary and extrapulmonary MTB infections. Abstract: Mycobacterium tuberculosis (MTB) can disseminate to extrapulmonary organs, particularly in severely immunosuppressed patients. Confirmation of active MTB infection is often difficult in subjects with a contraindication for invasive procedures. A case of disseminated MTB infection after hematopoietic stem cell transplantation is reported herein. Circulating cell-free DNA from the patient showed positive amplification of an MTB complex-specific sequence using a digital PCR technique. The MTB infection was confirmed by positive acid-fast staining and an approved quantitative PCR assay using liver tissue obtained at autopsy. The detection of MTB in circulating cell-free DNA using this technique may represent a less invasive diagnostic tool for pulmonary and extrapulmonary MTB infections.